Capacidades y desigualdad de género en el ámbito escolar: explorando las aspiraciones, la voz y otras capacidades de estudiantes del Callao - Sanoni Garcia, Piangella (2025)
The school is a space where knowledge is transmitted, but social inequalities are also reproduced. From the perspective of the capabilities approach, the school should be a place to expand students' capacities. This research seeks to explore gender differences in the expansion of capabilities such as aspiring, having a voice, receiving respect, recognition, self-esteem, and selfconfidence, and their relationship to gender inequality in the school environment. A qualitative approach was used, including thirteen semi-structured interviews, one focus group, and ten observations in the classroom and playground, analyzing the experiences of first-year secondary students in a public school in Callao. The results indicate that, regarding the capacity to aspire, girls face limitations due to gender stereotypes, while boys are restricted by ideals of masculinity. Regarding voice, girls participate less due to shyness and shame related to gender socialization, while boys dominate public spaces. The capacity to receive respect, recognition, selfconfidence, and self-esteem is limited for girls due to stricter discipline, and for both genders due to paternal absence. Additionally, bodily health is affected by factors such as violence and child labor. Finally, bodily integrity is restricted for both genders due to the tolerance of violence and harassment in school, with minimal intervention from authorities, which normalizes aggressive behavior, especially among boys.